2019
DOI: 10.1016/j.sleep.2019.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Objectively measured sleep duration and plasma glucose values following an oral glucose tolerance test amongst pregnant women with obesity in the UK

Abstract: Objectively measured sleep duration and plasma glucose values following an oral glucose tolerance test amongst pregnant women with obesity in the UK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Published studies show that self-reported and objectively assessed sleep duration is associated with blood glucose levels 13 , 33 . A limitation in these studies and our study is that physical activity related energy expenditure (EE) during pregnancy is not controlled for.…”
Section: Discussionmentioning
confidence: 99%
“…Published studies show that self-reported and objectively assessed sleep duration is associated with blood glucose levels 13 , 33 . A limitation in these studies and our study is that physical activity related energy expenditure (EE) during pregnancy is not controlled for.…”
Section: Discussionmentioning
confidence: 99%
“…Nocturnal sleep duration <7 h and later sleep midpoint were associated with statistically significant increased risk for GDM [ 26 ]. Finally, in another study short sleep duration was related to impaired glucose tolerance [ 27 ]. The findings are summarized at Table 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Women with longer CPAP use showed lower rates of preterm delivery, unplanned cesarean section, and hospitalization in NICU. Redfern et al, 2019 [ 27 ] UK 49 27–30 weeks 30–40 18–40 None Actigraphy None 75-g OGTT (NICE) Shorter sleep duration was associated with impaired glucose tolerance at 2 h during the OGTT. Balserak et al, 2020 [ 33 ] USA 92 24–36 weeks All 18–42 PSQI, ESS, SASS – MVAP index, habitual snoring Type I ΑΗΙ > 5 100-g OGTT (Carpenter-Coustan) or 50-g OGTT Incidence of OSA, frequency of snoring, SASS, and duration of REM sleep were greater in GDM group.…”
Section: Introductionmentioning
confidence: 99%
“…In pregnancy, epidemiological data have consistently shown strong associations between sleep quality, sleep duration, and maternal glycemia. 13,15,16 However, there is little research examining associations between other sleep disturbances, such as difficulty falling asleep and . CC-BY-NC-ND 4.0 International license It is made available under a is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity.…”
Section: Introductionmentioning
confidence: 99%